Quality of care in inflammatory bowel disease: actual health service experiences fall short of the standards. Issue 10 (27th October 2020) - Mikocka‐Walus, Antonina; Massuger, Wayne; Knowles, Simon R.; Moore, Gregory T.; Buckton, Stephanie; Connell, William; Pavli, Paul; Raven, Leanne; Andrews, Jane M.
Abstract: Background: Quality of care in inflammatory bowel disease (IBD) has received much attention internationally; however, the available surveys focus on health professionals rather than patients. Aims: To assess the experiences of healthcare for people living with IBD against established Australian IBD Standards. Methods: An online cross‐sectional survey was conducted with Australians ≥16 years old recruited via Crohn's & Colitis Australia membership, public and private clinics and the Royal Flying Doctor Service. Participants completed a questionnaire incorporating items addressing the Australian IBD Standards 2016, the Picker Patient Experience Questionnaire, IBD Control Survey and the Manitoba Index. Results: Complete data were provided by 731 respondents (71.5% female, median age 46 years, ranging from 16 to 84 years). While the majority (74.8%) were satisfied with their IBD healthcare, the care reported did not meet the Australian IBD Standards. Overall, 32.4% had access to IBD nurses, 30.9% to a dietician and 12% to a psychologist in their treating team. Participants managed by public IBD clinics were most likely to have access to an IBD nurse (83.7%), helpline (80.7%) and research trials (37%). One third of respondents reported waiting >14 days to see a specialist when their IBD flared. Participants received enough information, mostly from medical specialists (88.8%) and IBD nurses (79.4%). However, 51% wanted to be more involved in their healthcare. Conclusions: These data show discordance between expectations of patients and national standards with current levels of service provision, which fail to deliver equitable and comprehensive IBD care.